Analysis of CMOS Extended-Gate Field-Effect Transistor With On-Chip Window Based on Uricase/RuO2 Sensing Film - Po-Yu Kuo; Yung-Yu Chen; Wei-Hao Lai; Chun-Hung Chang (IEEE Journal of the Electron Devices Society)
In this study, the extended-gate field-effect transistor (EGFET) with an on-chip sensing window under the TSMC $0.18{μ }\text{m}$ 1P6M (one poly and six metals) CMOS process technology was fabricated as a biosensor. The sensing window was composed of six metal layers and functionalized with the ruthenium dioxide (RuO2) thin film and uricase for uric acid detection. The RuO2 thin film was deposited on the top metal layer of the sensing window using the radio frequency (RF) sputtering system. The silver probe was employed as a reference electrode to provide a voltage to the test solution with a micro-volume of $0.5 {μ }\text{L}$ . The properties of the EGFET for uric acid detection were investigated through the semiconductor parameter analyzer. The EGFET had a voltage and the current sensitivity of 8.63 mV/(mg/dL) and 0.17 ( ${μ }\text{A}$ ) $^{1/2}$ /(mg/dL), respectively. The device worked with a supply voltage lower than 1.8V. Based on the results, the fabrication of the miniaturized biosensor device was a success. Due to its advantages such as the use of low voltage and its simple fabrication process, it could help realize the development of a wearable biosensor.